2014
DOI: 10.1136/vr.102633
|View full text |Cite
|
Sign up to set email alerts
|

Standardised clients as assessors in a veterinary communication OSCE: a reliability and validity study

Abstract: In human medicine, standardised patients (SP) have been shown to reliably and accurately assess learners' communication performance in high-stakes certification Objective Structured Clinical Examinations (OSCE), offering a feasible way to reduce the need for recruitment, time commitment and coordination of faculty assessors. In this study, we evaluated the use of standardised clients (SC) as a viable option for assessing veterinary students' communication performance. We designed a four-station, two-track comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…In one study comparing scores of faculty members with those of actors trained as standardized clients and trained in use of a specific assessment tool, no difference in scores was identified. 23 In a study evaluating whether background of evaluators of OSCEs affected their scoring, there were significant differences in scores assigned by clinical science faculty members, basic science faculty members, faculty members who teach clinical communications, and hospital administrators/technicians, with those faculty who teach clinical communications assigning lower scores. 24 In the present study, it was also the clinical communications instructor who consistently scored students the lowest and it was the social worker, one of whose primary roles is to provide student support, who rated students the highest.…”
Section: Discussionmentioning
confidence: 99%
“…In one study comparing scores of faculty members with those of actors trained as standardized clients and trained in use of a specific assessment tool, no difference in scores was identified. 23 In a study evaluating whether background of evaluators of OSCEs affected their scoring, there were significant differences in scores assigned by clinical science faculty members, basic science faculty members, faculty members who teach clinical communications, and hospital administrators/technicians, with those faculty who teach clinical communications assigning lower scores. 24 In the present study, it was also the clinical communications instructor who consistently scored students the lowest and it was the social worker, one of whose primary roles is to provide student support, who rated students the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Although no study has yet reported the same benefits of web-based learning in veterinary medicine, this approach is expected to have the same potential in veterinary communication education. Use of virtual patients is considered as an effective way to assess students' communication skills in human medicine and as a potential communication assessment tool in veterinary medicine [2].…”
Section: Training On Veterinary Communication Skillsmentioning
confidence: 99%
“…For example, we acknowledge that when we developed and implemented our first communication OSCE, there were concerns with surrounding noise and lack of a private and individualized space for students to demonstrate their skills in privacy. Though the setting was not ideal, it was functional and cost effective (Artemiou et al, 2013;Artemiou et al, 2014).…”
Section: Consider That Less Can Be Good Enoughmentioning
confidence: 99%
“…We purposely used a 21-item rubric that was based on the Calgary Cambridge Guide (CCG) and an adapted form of the Liverpool Undergraduate Communication Assessment Scale (LUCAS); both instruments are validated in human medicine to evaluate students' communication skills and we adapted these for veterinary communication OSCEs (Artemiou et al, 2013). Likewise, we also implement the validated approach in human medicine of engaging standardized clients in portraying their assigned roles as well as being trained in the role of the assessor for our veterinary communication OSCE (Artemiou et al, 2014).…”
Section: Build Program On Evidence and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation